Life Cycle Analysis of Sotol Production in Mexico - Madrid-Solórzano, Juan Manuel; García-Alcaraz, Jorge Luis; Macías, Emilio Jiménez; Cámara, Eduardo Martínez; Fernández, Julio Blanco (Frontiers in Sustainable Food Systems, 2021)
Sotol is a Mexican distilled spirit of Mexican produced in Northern Mexico. The estimated annual production of sotol is at around 5200 hL per year. This industry grows at an average rate of five percent per year. The Mexican Sotol Council (MSC) and the Sotol Certificate Council (SCC) are regulatory bodies entities dedicated to monitoring that sotol producers must comply with the Official Mexican Standard NOM-159-SCFI-2004. Currently, those regulatory bodies entities try to improve the sotol production process and good practice guidelines to contribute generate a cleaner production. This paper reports a case study of artisanal sotol production in Chihuahua state in Mexico. Life Cycle Analysis Assessment (LCA) technique was used to compute the sotol is distilled spirit environmental impact performance to identify systems' hotspots and propose improvement interventions. SimaPro software v.9.1® is used for LCA, applying CML-IA baseline V3.05 / EU25 method to evaluate and select environmental impact categories. The system boundary included the stages of harvest, cooking, milling, fermentation, distillation, bottling, and packaging. Findings indicate that each of the stages required for sotol beverage processing significantly affects the marine ecosystem. The milling and bottling stages are the highest environmental impact. A 750 mL bottle of artisan sotol causes 5.92 kg CO2 eq, based on the empirical data. Sotol production houses makers should focus on reducing energy consumption caused by input transportation and equipment for milling.